Holly Qur'an: the key reference of materials - Al-Bat’hi, , Souad A. M.; Ahmad , Zuraida (Sci.Int.(Lahore), 2014)
The article basically focuses on some materials of different kinds that have been highlighted in the Holy Qur’an, particularly the Iron. Iron was the only kind of metal mentioned by name as sent down, in the Qur’an and has a whole sura entitled THE IRON or Al-Hadid, (57:25). Modern astronomical findings have disclosed that the iron found in our world has come from giant stars in outer space. By comparing those scientific findings to the Qur’anic verse (57:25), surat-lhadid, (The Iron), we noticed that the divine text and the scientific findings were conformed each other. And that the holy Qur’an has informed us earlier to the recent scientific discoveries. By that time no research was possible when the Holy Qur’an was revealed.